A study on the welfare equalization effect of China's housing reform - Mengyu Ding; Shaojie Zhou (Journal of Government and Economics, 2023)
The welfare equalization effect of China's housing reform is examined in this study using data from the China Urban Household Survey (CUHS) between 2002 and 2009. Low-income households who had access to housing reform homes (HRH) profited from the reform more than other low-income households, even though public housing was privatized at a reduced price due to quality restrictions and reselling constraints. We set up a model to demonstrate the mechanism, estimate household housing consumption, and analyze the impact of policy on that consumption. We find that the housing reform significantly increased the rate of homeownership in urban China, that the distribution of public housing and the privatization premium was comparatively equal, and that purchasing HRH significantly increased housing consumption. However, this effect also significantly decreased as household income increased. We refer to this welfare effect as bounded equalization. Additional housing policies should be developed to comprehensively offer low-income families affordable housing that meets their needs.